2013
DOI: 10.1200/jco.2012.45.0999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Socioeconomic Status on Access to Early-Phase Cancer Trials

Abstract: We show for the first time to our knowledge that socioeconomic status affects early-phase cancer trial referrals. The least-deprived patients are almost twice as likely to be referred compared with the most deprived. This may be because more-deprived patients are less suitable for a trial-as a result of comorbidities, for example-or because of inequalities that could be addressed by patient or referrer education. Once reviewed at the unit, enrollment onto a trial is not affected by deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Recently, the Clinical Trials Transformation Initiative (CTTI), a public-private partnership of more than 60 organizations from across the clinical trial enterprise, released a set of recommendations to guide study teams on how to efficiently and effectively plan for clinical trial recruitment (31). Attention should also be paid to enhancing accrual for minority and underserved patients who may otherwise be underrepresented, particularly in early phase trials (32, 33). Although more research is needed to further develop the evidence base for accrual, a number of resources and a curated library of relevant journal articles are available at NCI’s AccrualNet website (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Clinical Trials Transformation Initiative (CTTI), a public-private partnership of more than 60 organizations from across the clinical trial enterprise, released a set of recommendations to guide study teams on how to efficiently and effectively plan for clinical trial recruitment (31). Attention should also be paid to enhancing accrual for minority and underserved patients who may otherwise be underrepresented, particularly in early phase trials (32, 33). Although more research is needed to further develop the evidence base for accrual, a number of resources and a curated library of relevant journal articles are available at NCI’s AccrualNet website (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it can be assumed that an unbalanced distribution of GPs could translate into health inequities [38, 39]. A mismatched distribution of GPs constitutes a major challenge for public and community health.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior studies which have demonstrated that of patients who were successfully screened for phase I trials and who met eligibility criteria, age was not an independent factor of enrollment. (28, 29)…”
Section: Discussion/conclusionmentioning
confidence: 99%